Synthetic biology: at the crossroads of genetic engineering and human therapeutics—a Keystone Symposia report. Issue 1 (16th November 2021) - Cable, Jennifer; Leonard, Joshua N.; Lu, Timothy K.; Xie, Zhen; Chang, Matthew Wook; Fernández, Luis Ángel; Lora, José M.; Kaufman, Howard L.; Quintana, Francisco J.; Geiger, Roger; Lesser, Cammie F.; Lynch, Jason P.; et al.
Abstract: Synthetic biology has the potential to transform cell‐ and gene‐based therapies for a variety of diseases. Sophisticated tools are now available for both eukaryotic and prokaryotic cells to engineer cells to selectively achieve therapeutic effects in response to one or more disease‐related signals, thus sparing healthy tissue from potentially cytotoxic effects. This report summarizes the Keystone eSymposium "Synthetic Biology: At the Crossroads of Genetic Engineering and Human Therapeutics, " which took place on May 3 and 4, 2021. Given that several therapies engineered using synthetic biology have entered clinical trials, there was a clear need for a synthetic biology symposium that emphasizes the therapeutic applications of synthetic biology as opposed to the technical aspects. Presenters discussed the use of synthetic biology to improve T cell, gene, and viral therapies, to engineer probiotics, and to expand upon existing modalities and functions of cell‐based therapies. Abstract : Synthetic biology‐based therapies typically consist of engineered bacteria; viruses; or implantable, circulating, or tissue‐resident cells that are armed with the ability to secrete effector molecules, perform complex enzymatic transformations, or activate cellular activities based on signals from the environment. Synthetic biology therapeutics thereby offer the potential for increased specificity, as well as tunability, that can improve their therapeutic effectiveness and safety profile relative to molecule‐based therapies. On Demand content : https://keysym.us/21EK41NYAS